Fertility Decline in Iceland, 2013-2022: Trends and Structures - Jónsson, Ari Klængur (Comparative Population Studies, 2024)
Iceland is one of the Western countries that have experienced an unexpected fertility decrease in the 2010s. In this study, the aggregate Icelandic fertility decline is dissected to explore which fertility components are the main drivers behind the decline since 2010 in order to better understand whether the development is associated with compositional changes or linked to changes such as increased propensities of childlessness and decreased propensities to have another child. As such, it contributes empirical evidence to ongoing theorisation within current fertility debates. Official administrative register data are analysed by means of event-history analysis. Findings are presented as parity-specific birth risks and in the form of Kaplan-Meier estimates of synthetic period-based cohorts of women and men progressing to parity one over calendar years. In terms of results, we find that the fertility decline was concentrated around first births, and the decline can principally be attributed to women under the age of thirty. Propensities to remain childless have increased slightly since 2013, while there were no declines in the intensities to have a second and a third child. Hence, the development in Iceland appears to be driven by clear postponement of parenthood but not altered childbearing behaviour in terms of propensities to have a second and a third child. Results do not necessary contradict theories under the umbrella of the gender-relations framework, but they highlight the importance of exploring other factors impacting the transition to parenthood, such as perceived global and welfare uncertainties. Socioeconomic differentials in first-birth fertility and factors affecting postponement and ultimate childlessness should be explored further, as well as short-term developments in higher-order birth intensities during adverse circumstances, such as the 2008 economic crisis and the Covid-19 pandemic, during which periods the third-birth intensities increased.